Urgency of Government Policies in Developing Countries to Support Food Security to Prevent Hunger and Crime - Widodo, Guntarto (Yayasan pendidikan dzurriyatul Quran, 2026)
Food in Indonesia has a very important position, especially staple food, because it concerns political, economic, social and cultural problems. Most of the staple food of the population comes from cereals consisting of rice, corn and wheat and the largest as a staple food of the population is rice. Therefore, the issue of food security in Indonesia is important for political, economic, social and cultural stability. The government plays a strategic role in maintaining food security through various public policies designed to address complex challenges, such as limited agricultural land, climate change, fluctuations in food prices, and dependence on imports. The government's strategy in maintaining food security includes developing agricultural infrastructure, increasing productivity, diversifying food, strengthening the logistics system, and empowering communities and farmers as the main actors in the food sector.